The role of health literacy in predicting adherence to nutritional recommendations: A systematic review. Issue 1 (January 2018) - Carrara, Anna; Schulz, Peter J.
Highlights: First review on HL's impact on adherence to nutritional recommendations. HL was found scarcely determinant of patients' dietary adherence. Evidence on HL's impact on general public's nutrition behaviours is mixed. Most studies assessed only functional aspects of HL. Empowerment is likely to be a better determinant of patients' dietary adherence. Abstract: Objective: Synthesize quantitative empirical evidence on the role of health literacy in predicting adherence to dietary recommendations. Methods: A systematic search of 13 online databases resulted in 1498 articles eligible for screening. Of those, 20 met the predefined inclusion criteria and, together with 6 studies retrieved from their reference lists, were included for review. Screening of full-texts, data extraction and quality appraisal were independently performed by two reviewers. Inconsistencies regarding eligibility were resolved through discussion. Results: Of the 26 reviewed articles, 17 involved patients and 9 the general population. Overall, 35 associations between health literacy and various nutrition behaviours were observed. A significant direct positive association was reported in 5 cases, all of them concerning the general population. An insignificant association was reported in 20 cases, 15 of which were related to patients. The remaining associations were negative (n = 2), partially mediated (n = 1) or entirely mediated (n = 7). Conclusion: Health literacy was scarcely determinant of dietary adherence and other nutrition behaviours, especially among patients. Practice implication: Patients' dietary adherence is likely to be unaffected by interventions based on health literacy. Empowering approaches are expected to be more beneficial.